Formulasi Dan Uji Aktivitas Antioksidan Sediaan Gel Peeling Scrub Ekstrak Etanol Daun Teh Hijau (Camellia Sinensis) Asal Malino Dengan Metode DPPH - Azima Azima; Arham Febrianto; Nielma Auliah; Sri Wahyuningsih (Sasambo Journal of Pharmacy, 2026)
Abstract: Free radicals originating from both internal and external factors can cause skin damage such as premature aging and inflammation. Antioxidants are compounds that can neutralize free radicals, and one natural source is green tea leaves (Camellia sinensis), which are rich in flavonoids and polyphenols. This study aimed to formulate a peeling gel scrub from ethanol extract of green tea leaves from Malino and evaluate its antioxidant activity using the DPPH method. Extraction was carried out by maceration using 96% ethanol, and the gel was formulated in three extract concentrations (1%, 3%, and 5%). Physical evaluations included organoleptic, homogeneity, pH, viscosity, spreadability, adhesion, irritation, and stability tests (cycling test). Antioxidant activity was assessed using UV-Vis spectrophotometry and expressed as IC₅₀ values. The results showed that all formulas were physically and chemically stable and exhibited very strong antioxidant activity, with the lowest IC₅₀ value observed in the 5% formula at 22.13 ppm. Therefore, the green tea extract peeling gel scrub has potential as a natural-based topical cosmetic product effective as an antioxidant. Keywords: Green tea, peeling gel scrub, antioxidant, DPPH, IC₅₀